Analytical validation of the determination of the content of calcium carbonate in capsules by complexometric tritration - de Melo, Dênis Gomes; Campelo, Matheus da Silva; de Oliveira, Cristiani Lopes Capistrano Gonçalves; Ribeiro, Maria Elenir Nobre Pinho (Revista Contexto & Saúde, 2026)
People who suffer from calcium deficiency need supplementation to avoid diseases caused by low levels in the body, as this element performs several essential physiological functions in the human body. In this context, the present work aimed to validate a complexometric method for the determination of calcium carbonate in four different formulations, and the method validation followed the specifications of RDC 166/17 (ANVISA). The method proved to be selective, linear, accurate, precise and robust. The analytical curve showed a parametric and homoscedastic data distribution, with R2 > 0.99. In the analysis of precision and accuracy, relative standard deviation (RSD) values of less than 1.7% and recovery percentages above 98% were obtained, respectively, indicating that the method is precise and accurate. The application of the Youden method in the robustness study demonstrated the influence of the indicator on the methodology, while the other deliberate changes in the analytical method did not affect the response. In this way, a precise adjustment was made in the amount of the indicator to maintain the precision and accuracy of the methodology. The application of the validated classic method, as an environmentally friendly alternative, confirmed its potential for possible routine analysis applied to pharmaceutical forms in capsules.